The public rivalry between regulated and joint stock corporations and the development of seventeenth‐century corporate constitutions. Issue 248 (23rd December 2016) - Pettigrew, William A.; Stein, Tristan
Abstract: This article analyses the public debates about the two corporate forms used in the seventeenth century to develop England's international commercial reach: the regulated and joint stock company. It examines pamphlets to assess the changing public postures of the two forms across the period, and challenges histories of seventeenth‐century English overseas trade that argue the triumph of free trade over monopoly. The article instead suggests that the public debate about the two company forms contributed to the development of new corporate constitutions derived from both models and therefore recovers the neglected significance of the regulated company in this period.